Dansk kokkeforening af 1913. 25 Aars Jubilaeums-Festskrift. [Red. af E. Schüssel, Med Samarb. af C.J. Green Nielsen, H.P. Jørgensen, W. Svendsen m.fl.] ([Nielsen], 1938)
Med Avbr og Prtr. Udg. af Dansk Kokkeforening.